COMPARISON BETWEEN ANTHROPOMETRIC MEASUREMENT RESULTS BY CADRES AND MEDICAL PROFESSION STUDENTS USING TIPS (TIKAR PENDETEKSI STUNTING) - Siti Dwi Astuti; Lilik Zuhriyah; Alfryan Janardhana; Arum Sulistyarini; Indriani Ningrum; Rifqi Rinanto; Thalia Suharli; Rochelle siem; Zahra Zahra; Wandira Lalitya; Ahmad Ikbal P; Eleonora Sucahyo; Adeliza Firzarosany; Fariza Kusuma W; Helen Lioni; Ardy mahendra; Asrini Kaninta; Nafisa Naaz; Pedro gonzales; Proscilla Maiselina; Ekkel Aisyiyah; Nikma Fitriasari (Journal of Community Health and Preventive Medicine, 2023)
Stunting prevalence in District Kalipare on February 2019 was about 14%. Based on the results of the preliminary studies, one of the obstacles to achieving a free stunting rate is caused by anthropometric measurement errors by cadres. The objective of this study was to compare cadres of District Kalipare anthropometric measurement results with medical profession students' anthropometric results using the Tikar Pendeteksi Stunting (TIPS). This quasi-experimental study was conducted using a non-randomized control group pretest-posttest design. The sample of toddlers is 51 toddlers. The experiment was carried out by training 50 community-based health or posyandu cadres who were representatives from 8 villages in Kalipare District. Of the 50 cadres, 25 were selected by purposive sampling according to posttest scores per village. The selected cadres were asked to measure 1-3 infants or toddlers who had previously been measured before attending the training. The variables studied were nutritional status and height. The results showed that the Kappa test obtained a value of p = 0.838 or very good agreement. This study concludes that the results of height measurements by toddler posyandu cadres are the same as or close to the results of height measurements carried out by medical profession students. Therefore, after they have received training, we can include posyandu cadres in measuring anthropometrics.